Constructing Built‐in Electric Field in Ultrathin Graphitic Carbon Nitride Nanosheets by N and O Codoping for Enhanced Photocatalytic Hydrogen Evolution Activity. Issue 4 (29th December 2019) - Yan, Bo; Du, Chun; Yang, Guowei
Abstract: Codoping of N and O in ultrathin graphitic carbon nitride (g‐C3 N4 ) nanosheets leads to an inner electric field. This field restrains the recombination of photogenerated carriers and, thus, enhances hydrogen evolution. The layered structure of codoped g‐C3 N4 nanosheets (N‐O‐CNNS) not only provides abundant sites of contact with the reaction medium, but also decreases the distance over which the photogenerated electron–hole pairs are transported to the reaction interface. Quantum confinement in the ultrathin structure results in an increased bandgap and makes the photocatalytic reaction more favorable than bulk g‐C3 N4 . Under visible light irradiation, N‐O‐CNNS with 3 wt% Pt achieves a hydrogen evolution rate of 9.2 mmol g −1 h −1 and a value of 46.9 mmol g −1 h −1 under AM1.5 with 5 wt% Pt. Thus, this work paves the way for designing efficient nanostructures with increased separation/transfer efficiency of photogenerated carriers and, hence, increased photocatalytic activities. Abstract : An inner electric field in ultrathin g‐C3 N4 nanosheets is constructed through nitrogen and oxygen codoping. The doped impurities induce an electron density redistribution and then construct a built‐in electric field in ultrathin g‐C3 N4 nanosheets. The built‐in electric field restrains the recombination of photoinduced electron hole pairs, thus leading to an enhanced hydrogen evolution activity.